The Role and Challenges of Law Enforcement Agencies in Optimizing Eradication and Prevention of Money Laundering Crimes Involving Corporations - Usman Usman; Tubagus Achmad Darodjat (PT. Multidisciplinary Press Indonesia, 2024)
The large role of corporations in facilitating the occurrence of Money Laundering (TPPU) requires serious attention from the government and law enforcement. In Indonesia, money laundering cases often involve corporations operating in various sectors, indicating that corporations can function as a means to hide the proceeds of crime. One of the main challenges in eradicating Money Laundering is the lack of effective implementation of criminal sanctions against corporations. Criminal sanctions for corporations are an important instrument in law enforcement to prevent violations committed by business entities. Although Law Number 8 of 2010 has regulated criminal sanctions for corporations involved in Money Laundering, its implementation is still far from optimal. The research method used in this study is normative juridical with three approaches, namely the conceptual approach, the statutory regulatory approach, and the case approach. The results of the study indicate a vacuum of legal norms in Law Number 8 of 2010, which results in obstacles in the application of criminal sanctions against corporations involved in Money Laundering (TPPU). Therefore, it is necessary to update criminal law policy to correct the weaknesses contained in the law.